5
$\begingroup$

There are 4 equations. What should I put in place of the ? in the last one?

1 + 4 = 5
5 + 3 = 11
7 * 7 = 61
10 - 1 = ?
$\endgroup$
  • 2
    $\begingroup$ Is this an original question? If not, you should put the source in your puzzle text just to give due credit to its original author. $\endgroup$ – Xenocacia Mar 14 '18 at 6:54
  • 6
    $\begingroup$ My mother-in-law is author. How should I credit her? $\endgroup$ – asiniy Mar 14 '18 at 7:01
  • 4
    $\begingroup$ @asiniy Are you sure the second equation is not 5+3=10? $\endgroup$ – rhsquared Mar 14 '18 at 7:34
  • 3
    $\begingroup$ @asiniy You already did. Just by stating who's the author is crediting him/her. $\endgroup$ – Paul Karam Mar 14 '18 at 7:49
  • $\begingroup$ Has a correct answer been given? If so, please don't forget to $\color{green}{\checkmark \small\text{Accept}}$ it. If not, some responses to the answerers to help steer them in the right direction would be helpful. $\endgroup$ – Rubio Mar 17 '18 at 1:42
8
$\begingroup$

It looks to me like a simple octal calculation (i.e. base-8), assuming that there was an error on the second line. If this is the case then the answer is 7.

$\endgroup$
  • $\begingroup$ so you mean calculate in decimal then convert to Octal/Base 8? $\endgroup$ – ALinuxLover Mar 14 '18 at 10:59
  • 1
    $\begingroup$ @ALinuxLover No, I mean all the numbers are Base 8. $\endgroup$ – rhsquared Mar 14 '18 at 11:31
  • $\begingroup$ oh ok makes more sense heh $\endgroup$ – ALinuxLover Mar 14 '18 at 11:50
4
$\begingroup$

I guess the answer provided by @rhsquared is correct provided the OP corrects the question. But a more far fetched answer by assumption is

9 = 10-1 = 49 - (8*5) - From Normal Maths 10-1 = (7*7) - [(1+4)*(5+3)] - Rearrangement 10-1 = 61 - [5*8] -Substitution from above rules 10-1 = 61 - 55= 6. -Substitution from above rules & From Normal Maths

$\endgroup$
4
$\begingroup$

I think that one possible answer to the equations can be:

(Given data) + (3 * n * n) in which the n represents the iteration number, starting by 0.
(1 + 4) + (3 * 0 * 0) = 5 + 0 = 5 -> Iteration 0
(5 + 3) + (3 * 1 * 1) = 8 + 3 = 11 -> Iteration 1
(7 * 7) + (3 * 2 * 2) = 49 + 12 = 61 -> Iteration 2
(10 - 1) + (3 * 3 * 3) = 9 + 27 = 36 -> Iteration 3
Then, the answer is 36.

$\endgroup$
1
$\begingroup$

One possible answer using the previous answer and 2 to the power of the line index:

1 + 4 = 5
5 + 3 = 11 = 8 + (5-2^1)
7 * 7 = 61 = 49 + (11+5-2^2)
10 - 1 = 78 = 9 + (61+11+5-2^3)

$\endgroup$
  • $\begingroup$ But what if the last sum is alternating, where $10 - 1 = 38 = 9 + (61 - 11 + 5 - 2^3)\,?$ $\endgroup$ – Feeds Mar 21 '18 at 5:49
  • $\begingroup$ @user477343 an infinite number of solutions exist, and therefore an infinite number of "what ifs". The simplest solutions are preferred. $\endgroup$ – SwiftPanda Mar 21 '18 at 19:46
  • $\begingroup$ Yeah, I guess you might be right then. Perhaps the pattern was subtracting by $2^n$ instead of $2^n$ being the last summand of an alternating sum. My answer above was an entirely new pattern that I found, so maybe there are infinitely many patterns... $\endgroup$ – Feeds Mar 21 '18 at 20:50
1
$\begingroup$

I think the answer is

$10 - 1 = 23$

This is because,

The first prime after $(1 + 4) - 1 = 4$ is $5$. Notice that first corresponds to $1 = 2^0$. $\quad\qquad$ The second prime after $(5 + 3) - 3 = 5$ is $11$. Notice that second corresponds to $2 = 2^1$. $\quad$ The fourth prime after $(7\times 7) - 5 = 44$ is $61$. Notice that fourth corresponds to $4 = 2^2$.

Now, we do as follows:

We look at the fourth expression, namely ($10 - 1$), and then we subtract this by the next odd number from $5$, namely $7$, to make $$(10 - 1) - 7 = 2.$$ And now since $2^3 = 8$, we find the $8^\text{th}$ prime number after $2$, which is $23$. $$\therefore 10 - 1 = 23$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.